2017
DOI: 10.3847/1538-4357/aa78f4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Study of the Light Curve of PKS 1510-089 in GeV Energies

Abstract: We have analyzed data from the flat-spectrum radio quasar PKS 1510-089 collected over a period of eight years from 2008 August to 2016 December with the Fermi-LAT. We have identified several flares of this highly variable source, studied their temporal and spectral properties in detail, and compared with previous works on flares of PKS 1510-089. Five major flares and a few subflares or substructures have been identified in our study. The fastest variability time is found to be 1.30 ± 0.18 hr between MJD 55852.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 28 publications
7
32
0
Order By: Relevance
“…These time instants are completely ignored in our fastest variability analysis. The shortest variability time is found to be t var = 1.08±0.01 hr between MJD 57761.47 -57761.53; which is consistent with the hour scale variability found for other FSRQ like PKS 1510-089 (Prince et al 2017). We also found that the variability time during flares in Fermi-LAT data varies in the range of 1 hour to several days.…”
Section: Variabilitysupporting
confidence: 88%
“…These time instants are completely ignored in our fastest variability analysis. The shortest variability time is found to be t var = 1.08±0.01 hr between MJD 57761.47 -57761.53; which is consistent with the hour scale variability found for other FSRQ like PKS 1510-089 (Prince et al 2017). We also found that the variability time during flares in Fermi-LAT data varies in the range of 1 hour to several days.…”
Section: Variabilitysupporting
confidence: 88%
“…It is located at a redshift of z = 0.361 (Tanner et al 1996) with black hole mass 5.4×10 8 M ⊙ and accretion rate approximately 0.5 M ⊙ /yr (Abdo et al 2010). A long term analysis of the light curve of PKS 1510-089 with the eight year Fermi-LAT data has been done by Prince et al (2017) earlier. They have observed five major flares during 2008-2016, and their temporal and spectral features have been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…3(Abdo et al 2011), PKS 1510-089(Prince et al 2017)). There are four scenarios that are usually used to explain the observed spectral curvature/break (see, e.g.,Georganopoulos et al 2001;Abdo et al 2009;Poutanen & Stern 2010;Ackermann et al 2010;Stern & Poutanen 2014): 1) the "cooling break" resulting from the radiative losses of highenergy electrons, 2) the attenuation of high-energy photons by the extragalactic background light (EBL), 3) the transition of Compton scattering cross-section from the Thomson regime to the Klein-Nishina (K-N) regime, and 4) the photon-photon pair absorption associated with the He II Lyman continuum (LyC) or H LyC.…”
mentioning
confidence: 99%